PEMBELAJARAN PAI DIALOGIS, REFLEKTIF, DAN TRANSFORMATIF: SINTESIS DELIBERATIVE LEARNING, TRANSFORMATIVE LEARNING, DAN PEMBELAJARAN AGAMA OTENTIK - Rizqi Agus Kurniawan; Muhammad Fakhrur Rizal; M. Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rIslamic Religious Education (PAI) is expected to develop learners who possess not only religious knowledge but also critical thinking, reflective awareness, and the ability to apply Islamic values in real-life contexts. However, many learning practices remain teacher-centered, limiting opportunities for dialogue, critical reflection, and meaningful learning experiences. This study aims to develop a conceptual synthesis of dialogical, reflective, and transformative PAI learning through the integration of Deliberative Learning, Transformative Learning, and authentic religious learning. The study employed a Systematic Literature Review (SLR) by analyzing relevant scholarly publications retrieved from Google Scholar, ERIC, Garuda, and Scopus. The collected literature was examined using content analysis to identify, compare, and synthesize key findings related to the three learning approaches. The results indicate that Deliberative Learning promotes dialogical learning through discussion, argumentation, and respect for diverse perspectives; Transformative Learning strengthens reflective learning by encouraging critical reflection and perspective transformation; while authentic religious learning facilitates the internalization of Islamic values through contextual learning experiences. The integration of these three approaches produces a comprehensive conceptual framework that connects dialogue, reflection, and authentic experience into a coherent learning process. This conceptual synthesis contributes an alternative framework for developing Islamic Religious Education that is more participatory, meaningful, and responsive to the educational challenges of multicultural societies.